Polymer nanoparticles regulate macrophage repolarization for antitumor treatment. Issue 56 (22nd June 2021) - Fu, Xuancheng; Yu, Jiamu; Yuan, Anran; Liu, Libing; Zhao, Hao; Huang, Yiming; Shen, Song; Lv, Fengting; Wang, Shu
Abstract : Polymer nanoparticles regulate tumor-associated macrophage repolarization for imparting an antitumor effect and the combination with other therapies provides new ideas for drug delivery, macrophage regulation and immunotherapy in cancer treatment. Abstract : We demonstrate an intrinsic antitumor effect of polymer nanoparticles (P-NPs), which could re-program tumor-associated macrophages to pro-inflammatory phenotype. The intrinsic effect of P-NPs on macrophage repolarization and its combination with other therapies provide new ideas for drug delivery, macrophage regulation and immunotherapy in cancer treatment.